The role of systems support & maintenance in Business Process Innovation - Rashid, A; Wang, WYC; Tan, F. B. (Association for Information Systems (AIS), 2011)
There are an abundance of studies on examining the pre-adoption use and impact of information technology on organizations. In recent years, post adoption studies that relate to technology usage after it has been adopted, have started to appear in various research outlets but its scope remains limited. A great majority of these studies examined the post adoption related issues from technical perspective. This paper is an attempt to draw more attention to post adoption stage from a management perspective, and to define and present an initial set of factors that are likely to be involved in achieving business process innovation at the post adoption stage. In this paper, we present and explain antecedents of business process innovation having its basis in innovation dynamics literature. In sum, academics and practitioner contributions and implications by this research is also highlighted.